Croatia (Early Modern Period) - Štefanec, Nataša (Array, 2013)
Extensive annotated bibliography of studies on Croatian history in early modern period (16th-20th centuries) divided into chapters according to disciplinary and thematic principle. The author annotated monographs, important studies, PhD theses, journals, data and online resources in various relevant languages. Each chapter is followed by introductory study and comments.